(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—The growing complexity of modern power systems, coupled with the increasing integration of renewable energy sources, demands advanced control strategies to ensure enhanced power quality and system reliability. This study presents the implementation of novel control methodologies designed to mitigate power quality issues such as voltage fluctuations, harmonic distortions, and reactive power imbalances. The proposed control framework employs adaptive and intelligent algorithms, including model predictive control and artificial intelligence-based optimization, to dynamically stabilize system performance under varying load and generation conditions. Simulation and experimental results demonstrate significant improvements in voltage stability, reduced total harmonic distortion (THD), and enhanced overall system reliability. The findings highlight the potential of these innovative control strategies to support the development of robust, sustainable, and efficient power systems for future energy networks.